The lesbian revolution : lesbian feminism in the UK 1970-1990 - Jeffreys, Sheila (Routledge studies in radical history and politics, 2018)
The Lesbian Revolution argues that lesbian feminists were a vital force in the Women's Liberation Movement (WLM). They did not just play a fundamental role in the important changes wrought by second wave feminism, but created a powerful revolution in lesbian theory, culture and practice. Yet this lesbian revolution is undocumented.